Endoscopic variceal ligation combined with sclerotherapy for management of gastroesophageal variceal bleeding in pediatric patients: a single-center retrospective study - Li, Ming-Ming; Sun, Fang; Huai, Man-Xiu; Qu, Chun-Ying; Shen, Feng; Zhang, Yi; Xu, Lei-Ming (Frontiers in Pediatrics, 2024)
Objectives: Portal hypertension (PH) frequently gives rise to severe and lifethreatening complications, including hemorrhage accompanied by the rupture of esophageal and gastric varices. In contrast to the guidelines for the management of PH in adults, the optimal endoscopic management of variceal bleeding for secondary prophylaxis in children remains unclear. The present study evaluated the efficacy and safety of endoscopic variceal ligation (EVL) and endoscopic sclerotherapy (EST) to control bleeding in children. Methods: This retrospective study included 21 children with gastroesophageal variceal bleeding who underwent EST (n=13) or EVL (n=8) at Xinhua Hospital, Shanghai Jiaotong University School of Medicine, between February 2013 and March 2020.Short-term hemostasis rate and long-term rebleeding rate were evaluated. Adverse events related to the procedures, such as esophageal ulcer, esophageal stricture, abnormal embolization, pneumonia and perforation, were also recorded.Results: EVL and EST were performed successfully in all pediatric patients diagnosed with moderate to severe esophageal varices concurrent with gastric varices. Hemostasis was achieved during episodes of upper gastrointestinal bleeding. The mean volume of each single aliquot of cyanoacrylate injected was 0.3 ± 0.1 mL (range: 0.1-0.5 mL).Varices were eradicated in six (75%) of the eight patients who underwent EVL after a median 2 (range: 1-4) procedures and a median time of 3.40 months (range: 1.10-13.33 months). Eleven (52.4%) of the 21 patients developed rebleeding events, with the mean duration of hemostasis being 11.1 ± 11.6 months (range 1.0-39.2 months). No treatment-related complications, for example, distal embolism, occurred except for abdominal pain in one patient (4.8%).Conclusions: EST, alone or in combination with EVL, is an effective and safe method of managing variceal hemorrhage in children undergoing secondary prophylaxis.